Chemical, thermal, and microstructural characterization of polyethylene terephthalate composites reinforced with steel slag geopolymer waste - Medeiros Santos, Eliziane; Humberto Tommasini Vieira Ramos, Flávio James; Poubel Mendonça da Silveira, Pedro Henrique; Neves Monteiro, Sérgio; Vieira Gomes, Alaelson (Journal of Composites and Compounds, 2021)
The search for sustainable materials has grown globally due to the struggle against environmental impacts. From the recycling of PET packaging and the use of steel mill slag residue, from the steel production, it was developed in this work composites of PET matrix with additions of geopolymer obtained from steel mill slag. The composites were produced with concentrations of 0, 20, 40, and 60% of geopolymer and were characterized by XRD, FTIR, TGA, DSC, and SEM. The XRD analyses indicated the presence of mineral constituents referring to the geopolymer in the composites. Through the thermal analyses, it was observed that the addition of geopolymer promoted the increase in thermal stability, besides increasing the crystallinity in concentrations of 40 and 60% of geopolymer. From the micrographs, it was observed that the addition of reinforcement changed the morphology of the material, promoting an increase in the porosity of the material. From the characterizations, it is possible to state that the addition of geopolymers in the PET matrix produces low-cost composites with good properties and can be used in engineering applications.